Internet Addiction and Peer Relationship Difficulties: The Mediating Role of Sleep Disturbance - Romano, Giulia; Piskorz-Ryń, Oriana; Camilo Ríos, Juan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the mediating role of sleep disturbance in the relationship between internet addiction and peer relationship difficulties among adolescents.Methods and Materials: A descriptive correlational design was employed, and the study was conducted with 405 adolescents from Colombia, selected based on the Morgan and Krejcie sampling table. Participants completed three standardized instruments: the Internet Addiction Test (IAT), the Sleep Disturbance Scale for Children (SDSC), and the Peer Problems subscale of the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using Pearson correlation coefficients to examine bivariate relationships, and Structural Equation Modeling (SEM) was conducted using AMOS-21 to test the mediating model. The assumptions of normality, linearity, homoscedasticity, and multicollinearity were checked and confirmed.Findings: Internet addiction was significantly and positively associated with sleep disturbance (r = .52, p < .001) and peer relationship difficulties (r = .43, p < .001). Sleep disturbance also had a significant positive correlation with peer relationship difficulties (r = .47, p < .001). The SEM analysis confirmed an acceptable model fit (χ²(48) = 108.53, χ²/df = 2.26, GFI = .95, CFI = .96, RMSEA = .055). Direct effects were significant from internet addiction to sleep disturbance (β = .52, p < .001), sleep disturbance to peer difficulties (β = .41, p < .001), and internet addiction to peer difficulties (β = .33, p < .001). An indirect effect from internet addiction to peer difficulties via sleep disturbance was also significant (β = .21, p < .001), supporting partial mediation.Conclusion: The findings demonstrate that sleep disturbance plays a significant mediating role in the link between internet addiction and peer relationship difficulties. These results highlight the need for targeted interventions that address both digital behavior and sleep hygiene to improve adolescents’ social well-being.